2015
DOI: 10.1007/s00380-015-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhBNP on renal function in STEMI-HF patients with mild renal insufficiency undergoing primary PCI

Abstract: This study aims to investigate the effect of recombinant human brain natriuretic peptide (rhBNP) on renal function and contrast-induced nephropathy (CIN) incidence in ST-segment elevation myocardial infarction and heart failure (STEMI-HF) patients with mild renal insufficiency undergoing primary percutaneous coronary intervention (PCI). A total of 116 participants were randomized into rhBNP (rhBNP, n = 57) and nitroglycerin group (NIT, n = 59), receiving intravenous rhBNP or nitroglycerin from admission to 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…A previous study has shown that a reduced contrast volume can decrease the risk of CIN [5,17], especially in patients with renal dysfunction [18]. The mean contrast volume used has been reported to range from 218 to 303 ml in previous studies assessing CIN after primary PCI for ST-segment elevation AMI [2,3,[19][20][21].…”
Section: Discussionmentioning
confidence: 95%
“…A previous study has shown that a reduced contrast volume can decrease the risk of CIN [5,17], especially in patients with renal dysfunction [18]. The mean contrast volume used has been reported to range from 218 to 303 ml in previous studies assessing CIN after primary PCI for ST-segment elevation AMI [2,3,[19][20][21].…”
Section: Discussionmentioning
confidence: 95%
“…Five RCTs had a range of 1 to 6-month follow-up. In addition, 2 studies were performed in China [ 21 , 22 ] and the remaining 3 studies were conducted in the USA. [ 14 , 23 , 24 ] An RCT with >2 scores was considered to be high quality based on the Jadad scale.…”
Section: Resultsmentioning
confidence: 99%
“…The use of rhBNP had different mortality rate, with a range of 3.5% to 25.2%. [ 14 , 22 ] NIT treatment had also different mortality rate, with a range of 4.2% to 20.6%. [ 14 , 21 ] Readmission rate ranged from 7% to 61.1% in the rhBNP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Meanwhile, Qian et al reported in their research that prophylactic nitrates with matched adequate hydration is an effective strategy for CKD and CHF patients to prevent CIN. [16] Furthermore, rhBNP is effective in decreasing the incidence of CIN in patients suffering primary PCI, [17] and Acetylcysteine can be used to protect against CIN. [18] Ali-Hassan-Sayegh et al pointed out, when the patients with adequate hydration plus ascorbic acid, the incidence of CIN decreased significantly.…”
Section: Discussionmentioning
confidence: 99%